Investigating a tripartite collaboration between accounting firms, teachers and prospective accounting learners for growing the accountancy pipeline: a case study from Makhanda - Mrubata-Mhlebi, Nomahlubi (College of Accounting, 2025)
The accounting profession is experiencing a concerning decline in the number of people joining the profession. This is evidenced by decreasing enrolments in entrance examinations, smaller classes in university lecture theatres and the discontinuation of accounting classes in many high schools. Yet, the significance of this profession cannot be overstated in its role in fostering a robust local economy and providing its members access to a quality of life which surpasses that of the average individual. This study is qualitative in nature and follows a two-phase approach, firstly, using semi-structured interviews to collect data from a sample of twenty learners and six schools from four quintile three schools in Makhanda. The second phase required semi-structured interviews with participants from four accounting firms using the analysed data from phase 1 as a base. The theory of social justice is used as a lens to answer the following research question: How can the accounting profession, prospective accounting learners and their teachers collaborate to grow the pipeline of prospective accountants? Among others, the study finds that learners and firms can collaborate through school prize giving, formalised school visits and tailored career fairs. Teachers and firms can collaborate through the development of teaching and learning material and through firms acting as advisors when needed. The study is unique in its documentation of solutions that may assist in increasing the pipeline of prospective accountants. The findings of the study may be useful to academics and professionals concerned with the declining pipeline into the profession and those responsible for promoting the profession.